Current view on phylogeny within the genus Flabellula Schaeffer, 1926 (Amoebozoa: Leptomyxida) - Lisnerová, Martina (Jihočeská univerzita, 2022)
The present study deals with the molecular phylogeny of the genus Flabellula Schaeffer, 1926 that has been updated by determining SSU rRNA and actin gene sequences of 19 new strains. The descriptions of two novel species, F. schaefferi n. sp. and F. sawyeri n. sp., are provided based on the congruence of morphological data with SSU rRNA and actin gene sequence phylogenies, in-silico secondary structure prediction of the V2 region in the SSU rRNA, and by recognition of species-specific sequential motifs within this region.
Current view on phylogeny within the genus Flabellula Schaeffer, 1926 (Amoebozoa: Leptomyxida)
Keywords: Flabellula; Flabellulidae; amoeba